2011
DOI: 10.2528/pier11061304
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Metamaterial Modulators Based on Absorption

Abstract: Abstract-Metamaterial absorbers can perfectly absorb an incident wave in a narrow frequency band. In this paper, metamaterial absorbers are used to construct a terahertz modulator. By controlling the carrier density in the n-doped semiconductor spacer between a patterned metallic superstructure and a metallic ground with different applied voltage bias, the absorption varies sensitively, and the reflected wave amplitude acting as the modulated signal can be strongly modulated. Two types of modulators are invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…(v) Thus, the ILWC values lower than ILWC th are not considered as precipitations, with exception of those detected by CR 1 . To the best of our knowledge, this criterion should be established Liquid Precipitation Parameter (RRR): Accumulated Rain in previous 6 h > 1 mm CR 3 Liquid Precipitation Parameter (RRR): Accumulated Rain in following 6 h > 1 mm as the most reliable identificator of presence of rain during a radiosounding.…”
Section: Description Of the Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(v) Thus, the ILWC values lower than ILWC th are not considered as precipitations, with exception of those detected by CR 1 . To the best of our knowledge, this criterion should be established Liquid Precipitation Parameter (RRR): Accumulated Rain in previous 6 h > 1 mm CR 3 Liquid Precipitation Parameter (RRR): Accumulated Rain in following 6 h > 1 mm as the most reliable identificator of presence of rain during a radiosounding.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…Within this range, a considerable research effort is currently concentrated on technological developments aiming to improve characteristics and performance of devices for emitter and receiver systems. A very important number of comprehensive reviews [1,2] on the state-of-the-art of THz technology [3][4][5] can be found in the literature . A non-exhaustive list of applications includes astronomy [6], security scanning [7], explosives detection [8], medical imaging and biology [9,10] and atmospheric remote sensing [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although various components have been developed for THz applications [5][6][7][8][9][10][11][12][13][14][15][16][17][18], high power, low cost, and compact THz sources are not readily available [19]. With the rapid advancement of multi-physics based codes, which provide the possibility of simulating the nonlinear beam-wave interaction dynamics [20][21][22][23][24], extending the operating frequency of the existing microwave tube designs [25][26][27][28][29] has become a promising approach for developing compact and powerful THz sources [30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…The terahertz (THz) frequency region, which is loosely defined as 0.1-10 THz, has long been known as "the THz gap" although THz science and technology have made significant progress in the past decades [1][2][3][4]. The lack of suitable and efficient signal sources limits applications to a number of areas that demand highly reliable performance, ranging from molecular spectroscopy to astronomy, environmental monitoring, bio-imaging, and security screening [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%